Sejarah dan Perkembangan Pertanggungjawaban Korporasi - Hesti Widya Ningrum (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2018)
Corporate criminal responsibility has a difference in its development between countries with the common law system and those with civil law system. This is also, no exception in Indonesia. Indonesia as a Dutch Colony, which adheres to the civil law system which carries the adagium